AUTUMN MOTIF IN THE POETRY OF USMAN AZIM (Scientific journal of the Fergana State University, 2023)
This article is intended to define the harmony of nature and spirit through the motive of autumn in the poetry of Osman Azim. The article uses methods of comparative typological and biographical analysis. As a result, it was found that in the poetry of Osman Azim, the national type of landscape is more pronounced in terms of the seasonal landscape, the level and scale of the landscape in terms of spatio-temporal characteristics. "Autumn" is the result of the poet's life, the vital conclusions of the period of maturity and the observational poetic interpretation of his philosophical observations. When analyzing the chronology of Osman Azim's works, it is noted that the image of "autumn" first becomes a symbol of fatigue and hopelessness, that is, a feeling of separation from the mood of happiness. From the rest of the seasons, it can be seen that the "winter" landscape has two different meanings. The seasons are an aspect that enriches the content of Osman Azim's work. In this regard, we believe that a seasonal study of his work could be a good subject for future research. In the poems of Osman Azim, nature appears in poetry not only as an aesthetic value, but also as a high moral category. In his poems, Osman Azim depicts with deep drama the pains of the human heart, eternal sorrows, comparing them with natural landscapes.